Palaeoflood activity and climate change over the last 1400 years recorded by lake sediments in the north‐west European Alps. (13th February 2013) - Wilhelm, B.; Arnaud, F.; Sabatier, P.; Magand, O.; Chapron, E.; Courp, T.; Tachikawa, K.; Fanget, B.; Malet, E.; Pignol, C.; Bard, E.; Delannoy, J. J.
Abstract A high‐resolution sedimentological and geochemical study of a high‐altitude proglacial lake (Lake Blanc, Aiguilles Rouges, 2352 m a.s.l.) revealed 195 turbidites, 190 of which are related to flood events over the last 1400 years. We used the coarsest sediment fraction of each turbidite as a proxy for the intensity of each flood event. Because most flood events at this locality are triggered by localized summer convective precipitation events, the reconstructed sedimentary record reveals changes in the frequency and intensity of such events over the last millennium. Comparisons with other temperature, palaeohydrological and glacier reconstructions in the region suggest that the most intense events occurred during the warmest periods, i.e. during the Medieval Climate Anomaly (AD 800–1300) and the current period of global warming. On a multi‐decadal time scale, almost all the flood frequency peaks seem to correspond to warmer periods, whereas multi‐centennial variations in flood frequency appear to follow the regional precipitation pattern. Consequently, this new Alpine flood record provides further evidence of a link between climate warming and an increase in the frequency and intensity of flooding on a multi‐decadal time scale, whereas the centennial variability in flood frequencies is related to regional precipitation patterns. Copyright © 2013 John Wiley & Sons, Ltd.